A dual-functional social innovation process model for low-cost houses through university-enabled initiative - Belayutham, Sheila; Ibrahim, Che Khairil Izam Che; Zulkifli, Assrul Reedza; Ibrahim, Norhati (Construction Innovation-England, 2019)
The purpose of this study is to develop a dual-functional university-enabled social innovation process model on the subject of low-cost houses that addresses the distinct elements of social obligation and university teaching-learning. Design/methodology/approach This study has predominantly adopted a longitudinal single case study approach, where data have been collected through interviews, survey, participant observation, direct observation and document review. The case study details on the social innovation processes, which was conducted by Universiti Teknologi MARA, Malaysia. Findings This study has demonstrated the social innovation processes toward addressing the issue of insufficient low-cost houses, concurrently benefitting the teaching-learning dimension. Three sub-innovations have been highlighted in the developed social innovation process model, which are collaboration process, teaching-learning and design-construct innovation. Originality/value The development of the social innovation process model for low-cost houses through university-enabled initiative is a novel establishment, particularly for developing nations, as limited studies have been conducted in this regard. The significant insights into how university could play a role in addressing major social issues, along with their core focus (teaching-learning and research development), is a breakthrough for further diffusions of social innovation by universities.
Keywords: Asie; Enseignement; Innovation sociale; Recherche; Rôle des universités; logement